1998
DOI: 10.12693/aphyspola.94.309
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Structural Properties of Zn1-xBexSe Mixed Crystals

Abstract: Optical and structural properties of Ζn 1 -x Bex Se bulk crystals in the range of composition 0 _ < x < 0.41 have been studied. These crystals were grown by Bridgman method under an argon overpressure. Transmission, absorption, photoluminescence and photoacoustic spectra as a function of composition were investigated. It has been found that the crystal structure is of sphalerite type. The crystal quality increases when the crystallization process of the same boule is performed more than once. In the investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
(5 reference statements)
2
0
0
Order By: Relevance
“…This is in conformity with the observation, that increasing Be and Mn concentration in Zn 1-x-y Be x Mn y Se causes increase the lattice rigidity of the material [23]. …”
Section: Resultssupporting
confidence: 93%
“…This is in conformity with the observation, that increasing Be and Mn concentration in Zn 1-x-y Be x Mn y Se causes increase the lattice rigidity of the material [23]. …”
Section: Resultssupporting
confidence: 93%
“…It was observed that for concentration of beryllium larger that about 0.1 only yellow emission is observed in the temperature range from 34 K to room temperature. This is in agreement with the observations for Zn 1-x Be x Se crystals grown by the same method [3] where the intensity of exciton emission decreased with increasing of Be content. For this reason, determination of the energy gap from lumines- cence data is not possible for crystals with high Mn content.…”
Section: Luminescencesupporting
confidence: 92%